Estudo biológico de linhagens do protozoário ciliado Paramecium Caudatum Ehrenberg, 1833 e avaliação experimental do efeito tóxico do agrotóxico Fipronil - Alves, Henrique Cezar (Universidade Federal de São Carlos, 2010)
Protozoans has been proposed as biological indicators of water pollution due to their sensitivity to environmental changes, their short life cycle and easy cultivation, this work intended to study two strains of the ciliated protozoan Paramecium caudatum Ehrenberg, 1833 (PC1 isolated from the Monjolinho Reservoir - São Carlos-SP and maintained in monoxenic culture at the Laboratory of Ecology of Aquatic Microorganisms of UFSCar and PC2 isolated from Óleo Lagoon an oxbow lake in the Moji-Guaçu River floodplain Luiz Antônio- SP). Experiments were done aiming to study the life cycle, best cultivation conditions and to verify the toxicity of the pesticide fipronil to these protozoan lineages, considering that the local from which they were isolated have differing history of contamination with the pesticide. The experiments were executed aiming to verify the possibility of the utilization of these organisms as environmental bioindicators in a standardized bioassay. The best culture condition obtained for PC1 was at pH 9 and 30 °C and for PC2 was at pH 7 and 27.5 °C. For the two lineages the best results were obtained with no light and agitation and the increase of the cultivation scale not interfered significantly in the growth. It was possible to observe that in culture, the PC2 has a slower growth and, in the other hand higher densities than PC1. Compared with other organisms, the two lineages are very resistant to fipronil, and as a result not suitable as bioindicators of environmental contamination by this pesticide. Besides, because they are food items for the higher trophic levels, their resistance to the pesticide led us to consider that in the contaminated ecossystems, these organisms can be important for the fipronil accumulation in the food web. However, the studied ciliates displayed potential to be used as test-organisms for ecotoxicological assays.
Keywords: Biotecnologia; Cultivo monoxênico; Toxicidade testes; Curva de crescimento; Fixadores; Otimização de cultivo; Agrotóxico; Protozoário; Fixatives; Monoxenic culture; Toxicity; Culture optimization; Growth curve; Pesticide; Protozoan; CIENCIAS BIOLOGICAS::FARMACOLOGIA::TOXICOLOGIA